The Effect of Computer Supported Collaborative Learning (CSCL) Assisted with E-Learning on Students’ Creativity in Simulation and Digital Communication - Fadil Firdian; Liranti Rahmelina (Faculty of Engineering, Universitas Negeri Yogyakarta, 2021)
Previous studies have suggested that Computer Supported Collaborative Learning (CSCL) learning is effectively applied in education. However, prior research has only focused on the impact of CSCL on learning achievement and has not examined students' creativity in the learning process. This study aims to examine the CSCL assisted with e-learning media to increase students’ creativity. This study was a quantitative study with a quasi-experimental method. The research design was a pretest-posttest control group design. The validity was determined using content validity, and two experts confirmed that the instrument was acceptable. The normality and homogeneity tests were used in the prerequisite test while a t-test was used to test hypotheses. The findings reported that: (1) after learning with the CSCL assisted with e-learning media, 18.75% of students were categorized as very creative, 43.75% of students were creative, and 37.5% of students were in the acceptable category (3) the CSCL model assisted with e-learning media impact positively to the students’ creativity based on the results of the t-test proved by t count was higher than t table, namely 6.112 2.04, with a smaller significant value of 0.05 (p = 0.00 0.05). Furthermore, the results showed the gain score from four indicators of creativity was 0.655 with moderate interpretation where the highest skill was fluent thinking. As a result, students were creative in executing product design concepts after implementing the CSCL assisted with e-learning media.